2017
DOI: 10.2147/ijn.s149107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dacarbazine on CD44 in live melanoma cells as measured by atomic force microscopy-based nanoscopy

Abstract: CD44 ligand–receptor interactions are known to be involved in regulating cell migration and tumor cell metastasis. High expression levels of CD44 correlate with a poor prognosis of melanoma patients. In order to understand not only the mechanistic basis for dacarbazine (DTIC)-based melanoma treatment but also the reason for the poor prognosis of melanoma patients treated with DTIC, dynamic force spectroscopy was used to structurally map single native CD44-coupled receptors on the surface of melanoma cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…The results demonstrated DTIC affects, but not completely inhibits, the binding of CD44 ligand to membrane receptors, suggesting the reason for the poor prognosis associated with DTIC treatment of melanoma. Therefore, AFM gives thermodynamic and kinetic insights into the effect of DTIC on the CD44 ligand-binding process (Hj et al, 2017). Bobrowska et al (2019) also demonstrated that vertical growth phase melanoma cells showed surface biochemical and biomechanical changes in parallel, which could be used as a fingerprint of melanoma progression (Bobrowska et al, 2019).…”
Section: Metastizationmentioning
confidence: 99%
“…The results demonstrated DTIC affects, but not completely inhibits, the binding of CD44 ligand to membrane receptors, suggesting the reason for the poor prognosis associated with DTIC treatment of melanoma. Therefore, AFM gives thermodynamic and kinetic insights into the effect of DTIC on the CD44 ligand-binding process (Hj et al, 2017). Bobrowska et al (2019) also demonstrated that vertical growth phase melanoma cells showed surface biochemical and biomechanical changes in parallel, which could be used as a fingerprint of melanoma progression (Bobrowska et al, 2019).…”
Section: Metastizationmentioning
confidence: 99%
“…It has been shown that CD34 and CD44 play a key role in the regulation of several properties of CSCs, such as self-renewal, metastasis, tumor initiation, chemo-and radio-resistance, and colonization [18,19].For this reason, in the present study, the expression levels oftwo cell-surface markers, i.e.CD34 and CD44, were examined before and after treatment with metformin by ow cytometry.CD34 is a glycoprotein expressed on hematopoietic stem cells and capillary endothelial cells. CD34 has been found to be over expressedin aggressive tumor cells and this has been veri ed by molecular methods [12]. In this study, as suggested in some previous studies, we assumed that this molecule could be related to endothelial and stemness phenotype in tumor cells and facilitate cell migration [6,18].…”
Section: Resultsmentioning
confidence: 57%
“…Some studies have shownthat the CD44 ligand-receptor complexes on dacarbazine-treated melanoma cells are less stable than on untreated cells. However, the CD44 receptor could still be activated, which, in turn, could lead to the activation of intracellular signaling and, consequently, a cellular response [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cancer research, AFM can be used as a high-imaging technique to analyze morphological changes for the evaluation of drug effects. Further, mesenchymal stem cell shape is changed during chondrogenic induction [ 18 ]. While changes of cell shape appear to be necessary for differentiation, little is known about whether cell morphology affects earlier developmental stages of mesenchymal stem cell differentiation.…”
Section: Resultsmentioning
confidence: 99%